2001
DOI: 10.1088/0960-1317/12/1/306
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligning microfluidic interconnects for glass- and plastic-based microfluidic systems

Abstract: In this work, we present novel self-aligning fluidic interconnection techniques with low dead volume and pressure drop for generic microfluidic systems and capillary electrophoresis chips. We have successfully designed, fabricated and characterized two self-aligning fluidic interconnection techniques in this work, both resulting in low dead volume and low pressure drop across the interconnects. The first technique is a serial assembly technique, in which each fluidic interconnect is assembled individually, exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 8 publications
2
54
1
Order By: Relevance
“…Puntambekar and C.H. Ahn designed couplers with cavities in the top layer of a microfluidic system [66]. The system was heated up and tubing with an insert was put into the couplers, melting and filling the cavities.…”
Section: E Meng Et Al Designed Several Couplers For Silicon Based Mmentioning
confidence: 99%
“…Puntambekar and C.H. Ahn designed couplers with cavities in the top layer of a microfluidic system [66]. The system was heated up and tubing with an insert was put into the couplers, melting and filling the cavities.…”
Section: E Meng Et Al Designed Several Couplers For Silicon Based Mmentioning
confidence: 99%
“…Furthermore, this kind of permanent interconnection is time consuming in the alignment and assembly process. In order to overcome the disadvantages of this permanent interconnection, reversible interconnections were developed (Zhen and Maeda 2003;Snakenborg et al 2007;Sabourin et al 2009;Nittis et al 2001;McDonald and Whitesides 2002;Zhen and Maeda 2002;Puntambekar and Ahn 2002;Pattekar and Kothare 2003;Bhagat et al 2007Perozziello et al 2008Yao et al 2000;Peles et al 2004;Lee et al 2004;Chiou and Lee 2004;Pepper et al 2007;Christensen et al 2005;Dalton and Karan 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to dip the tip of a capillary tube in liquid nitrogen to temporarily shrink it and then fit it in cylindrical hole with diameter slightly less than capillary OD at room temperature. Other methods for making capillary connections have also been introduced, such as using polymer sealant and melting the capillary tip into the inlet hole as presented by Tsai et al (2001), Puntambekar et al (2002), Pattekar and Kothare (2003) and Kovacs (1999). Alternatively, it is also possible to use couplers to ease aligning and sealing.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Gray et al (1999) reported several micromachined interconnects using a combination of silicon fusion bonding and deep reactive ion etching. Puntambekar and Ahn (2002) fabricated a self-aligned fluidic interconnect with low dead volume and pressure drop (2002). Tsai and Lin (2001) developed a microfluidic interconnect with an integrated Mylar sealant.…”
Section: Introductionmentioning
confidence: 99%